2018
DOI: 10.1007/s00330-018-5842-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver microwave ablation: a systematic review of various FDA-approved systems

Abstract: Objectives The aim of the present study is to analyze preclinical and clinical data on the performance of the currently US Food and Drug Administration (FDA)–approved microwave ablation (MWA) systems. Methods A review of the literature, published between January 1, 2005, and December 31, 2016, on seven FDA-approved MWA systems, was conducted. Ratio of ablation zone volume to applied energy R(AZ:E) and sphericity indices were calculated for ex vivo and in vivo experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 51 publications
1
55
0
Order By: Relevance
“…Comparing these results, we see that our results of 3.2 mm lie within the range of 3.1 to 5.3 mm reported in literature. Given, the high unpredictability of ablation zones with a given power/time setting, we see the ablation validation using a post‐ablation control scan as a crucial step for obtaining reliable tumour control in one session. In our treatment algorithm, the ablation prediction (based on manufacturer's datasheets) is used as an estimate for the required ablation energy.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these results, we see that our results of 3.2 mm lie within the range of 3.1 to 5.3 mm reported in literature. Given, the high unpredictability of ablation zones with a given power/time setting, we see the ablation validation using a post‐ablation control scan as a crucial step for obtaining reliable tumour control in one session. In our treatment algorithm, the ablation prediction (based on manufacturer's datasheets) is used as an estimate for the required ablation energy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved to be safe and effective for the treatment of liver cancer, renal cancer and thyroid nodules, and has become an alternative of surgery in these fields [16][17][18]. Up to now, there has been several options of thermal ablation such as microwave ablation (MWA), radiofrequency ablation (RFA), laser ablation (LA), and high-intensity focused ultrasound (HIFU) [16,[19][20][21][22]. Compared to surgical treatment, local ablation remains to be a relatively simple procedure, easily tolerant for patients, with fewer complications, a shorter hospitalization and convalescence period [23].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of energy needed can also be planned with the planning software. However, recent studies have shown that the resulting ablation zones differ from the prediction based on the ex-vivo results that are provided by the ablation device manufacturers [26] and also depend on the tumor type [27].…”
Section: Ablationmentioning
confidence: 91%
“…The ablation model presented in the brochures is described as an ellipsoidal or spherical volume, which was obtained from measuring the ablation necrosis in ex-vivo, non-perfused, healthy animal livers. Recent studies have shown that the in-vivo ablation volumes differ significantly from the ex-vivo data, with the in-vivo ablation volumes being much smaller than the ex-vivo data predicts [26,35]. Future models will be based on retrospective invivo data and also take any clinical parameters into account, such as the pathology of the tissue, the patient's clinical background, other treatments being administered (e.g., chemotherapy), and the influence of adjacent blood vessels on the expansion of the ablation volume.…”
Section: Ablation Zone Predictionmentioning
confidence: 94%